1991
DOI: 10.1007/bf00218673
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hyperthermia during pregnancy and cardiovascular malformations in the offspring

Abstract: During pregnancy, a number of factors predisposing to hyperthermia, such as sleeping in a water bed, sauna bathing, heatwave, high workplace temperature, and fever, are believed capable of harming the foetus. This study aimed to clarify possible associations of maternal workplace temperature, season of birth, sauna bathing, upper respiratory infection, and fever, with cardiovascular malformations in the offspring. The material was composed of all 573 cardiac malformations registered in Finland in 1982-84, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 24 publications
4
49
0
1
Order By: Relevance
“…No association was found between maternal sauna REVIEW bathing, the course of gestation, or the occurrence of congenital defects in a Finnish study (a three-year national material with about 500 cases and 1000 healthy control babies) (49). Similar results on the use of hot baths and sauna have been reported from New York (50).…”
Section: Pregnancysupporting
confidence: 69%
“…No association was found between maternal sauna REVIEW bathing, the course of gestation, or the occurrence of congenital defects in a Finnish study (a three-year national material with about 500 cases and 1000 healthy control babies) (49). Similar results on the use of hot baths and sauna have been reported from New York (50).…”
Section: Pregnancysupporting
confidence: 69%
“…61 More recent studies suggest that other maternal febrile illnesses during the first trimester of pregnancy also may be associated with an increased risk for certain heart defects. 6,15,62,63 Mothers reporting any febrile illnesses during the first trimester of pregnancy have a 2-fold-higher risk of offspring with any heart defect in these studies. 6,15 Specific groups of defects that have been shown to be associated with maternal febrile illness include pulmonic stenosis, 6 all right-sided obstructive defects, 15 tricuspid atresia, 6,15 coarctation of the aorta, 15 all left-sided obstructive defects, 15 conotruncal defects, and VSDs.…”
Section: Rubella Febrile Illnesses and Influenzamentioning
confidence: 82%
“…First, the hyperthermia-induced isolated neural-tube defects were described (Chance and Smith, 1978;Miller et al, 1978;Layde et al, 1980;Shiota, 1982;Milunsky et al, 1992;Shaw et al, 1998;Medveczky et al, 2004;Á cs et al, 2005a,b). In addition, a higher risk for some other ICAs such as microcephaly , microphthalmia (Fraser and Skelton, 1978) Hirschprung disease (Lipson, 1988), CAs of the abdominal wall (Little et al, 1991), cardiovascular CAs (Tikkanen and Heinonen, 1991;Botto et al, 2001;Á cs et al, 2005a, CAs of the urinary tract (Abe et al, 2003), and orofacial cleft (Métneki et al, 2005;Á cs et al, 2005a was also found after high feverrelated maternal diseases. However, as far as we know, the possible association between high fever and MCAs in the human being has not been published.…”
Section: Discussionmentioning
confidence: 93%